About experience in casting processes simulation - D. M. Koukoui; O. E. Shwarts; E. G. Shwarts; A. V. Zablotskiy; V. L. Akulitch (Литьë и металлургия)
Authors depict the particularities of casting process simulation with use ProCast packet.